BRS-Based Robust Secure Localization Algorithm for Wireless Sensor Networks - Ning Yu; Lirui Zhang; Yongji Ren (International Journal of Distributed Sensor Networks)
Localization is the key supporting technology for wireless sensor networks (WSNs). Security and accuracy are the premise of the localization application. Real-world applications of wireless sensor networks are often subject to a variety of adverse circumstances interference, and the localization performance is seriously affected. In this paper, we propose a BRS-based robust secure localization (BRSL) algorithm in order to reduce the impact of the malicious attackers in WSNs. The BRSL method includes two phases. In the first stage, the trust evaluation framework is established on the basis of beta reputation system. In the second phase, we employ the weighted Taylor-series least squares method to estimate the coordinates of sensor nodes. Simulation results demonstrate that the proposed algorithm is robust and effective.